The AlMo0.5NbTa0.5TiZr refractory high entropy superalloy: Experimental findings and comparison with calculations using the CALPHAD method. (May 2022) - Suárez Ocaño, Patricia; Fries, Suzana G.; Lopez-Galilea, Inmaculada; Darvishi Kamachali, Reza; Roik, Janina; Agudo Jácome, Leonardo
Graphical abstract: Highlights: Microstructural characterization of the AlMo0.5 NbTa0.5 TiZr refractory superalloy in the as-cast state is reported for the first time and compared with hitherto known annealed state. The detailed CALPHAD analysis with Scheil-Gulliver and equilibrium calculations reveal new insights into understanding the nature of the studied alloy by comparing with the experimental data. The equilibrium-based CALPHAD approach used here pinpoints the presence of a miscibility gap between two bcc-based phases, confirming the hypothesis that this alloy is formed by spinodal decomposition. Differential thermal analysis was reported for the first time for this alloy, revealing a good agreement between measured phase transformation temperatures and calculated values. Abstract: Detailed microstructural characterization of the AlMo0.5 NbTa0.5 TiZr refractory high entropy superalloy in the as-cast state is reported for first time and compared with the state annealed at 1400 °C for 24 h. The former shows a dendritic structure, with a mixture of A2/B2 phases < 20 nm in both the dendritic and interdendritic regions. A mostly amorphous phase, rich in Al and Zr, is found within the interdendritic region. The annealed state reproduced the combination of A2/B2/Al-Zr-rich phases reported previously. Calculations from two relevant ThermoCalc databases were compared with the experimental results. Equilibrium calculations were compared with results for the annealed alloy, whereas solidification paths calculated using Scheil-Gulliver model were used for comparison with the as-cast alloy. A previously hypothesized spinodal decomposition during cooling as the mechanism responsible for the patterned A2/B2 microstructure is confirmed via the CALPHAD calculations, pointing to its use as an efficient design tool for such alloys. Finally, the comparison between the experimental and computational findings allowed better understanding the solidification path and equilibrium stability of this alloy, giving a base to make better decisions on the field of new refractory superalloy design.